The wildland-urban interface in Poland reflects legacies of historical national borders - Kaim, Dominik; Helmers, David P.; Jakiel, Michał; Pavlačka, Daniel; Radeloff, Volker C. (Landscape ecology, 2023)
Context The wildland-urban interface (WUI) is an area where houses are located near wildland vegetation. As such, the WUI is a focal area of wildfire risk, human-wildlife conflicts, and other human-nature interactions. Although there is a wide consensus on the impact WUI existence might have, little is known about the WUI spatial determinants over long periods, especially in countries with long settlement history. Objectives Our goal here was to map the WUI across Poland, and to quantify the extent to which historical legacies shape current WUI pattern, since Poland is one of the countries, which experienced substantial political changes over time, which had an impact on historical settlement development. Methods We analysed a database of nearly 15 million building locations and a 10-m Sentinel-2-based land cover map to produce a country-wide WUI map of Poland. Then we compared the WUI pattern among parts of Poland which belonged to different political entities in 1900s and 1930s and also among different ecoregions. Lastly, we verified the effects of the historical borders or landscape units borders on WUI patterns with a discontinuity analysis. Results We found that a substantial part of Poland is WUI, and over 60% of all buildings are in WUI. However, WUI patterns differ considerably across the country, and WUI hotspots are located around the largest metropolitan areas in central and southern part of Poland and in the Carpathians. Furthermore, WUI patterns reflect pre-1945 national borders indicating long-term legacies of past settlement patterns and urban planning approaches. Diversity among ecoregions was much less pronounced than among past political entities. Conclusions Our work shows that current WUI pattern is to large extent shaped by former political conditions, which is likely true not only in Poland, but also in many parts of Europe and elsewhere where settlement history goes back centuries.